Functional breakdown of the lipid bilayer of the myelin membrane in central and peripheral nervous system by disrupted galactocerebroside synthesis - Bosio, Andreas (The National Academy of Sciences of the USA, 1996)
The lipid bilayer of the myelin membrane of the central nervous system (CNS) and the peripheral nervous system (PNS) contains the oligodendrocyte- and Schwann cell-specific glycosphingolipids galactocerebrosides (GalC) and GalC-derived sulfatides (sGalC). We have generated a UDP-galactose ceramide galactosyltransferase (CGT) null mutant mouse (cgt(−/−)) with CNS and PNS myelin completely depleted of GalC and derived sGalC. Oligodendrocytes and Schwann cells are unable to restore the structure and function of these galactosphingolipids to maintain the insulator function of the membrane bilayer. The velocity of nerve conduction of homozygous cgt(−/−) mice is reduced to that of unmyelinated axons. This indicates a severely altered ion permeability of the lipid bilayer. GalC and sGalC are essential for the unperturbed lipid bilayer of the myelin membrane of CNS and PNS. The severe dysmyelinosis leads to death of the cgt(−/−) mouse at the end of the myelination period.